2005
DOI: 10.1037/0735-7044.119.6.1448
|View full text |Cite
|
Sign up to set email alerts
|

Corticotropin-releasing factor-1 receptors in the basolateral amygdala mediate stress-induced anorexia.

Abstract: Corticotropin-releasing factor (CRF) receptor activation within the basolateral amygdala (BLA) has been relatively unexplored compared with the central nucleus of the amygdala (CeA), despite the fact that CRF receptors are more densely distributed in BLA than in CeA. The authors show that infusion of CRF into BLA, but not CeA, decreases feeding and increases grooming. These effects are mediated by CRF-sub-1 receptors, because they are blocked by intra-BLA treatment with NBI27914 (NBI), a CRF-sub-1 antagonist, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
36
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 42 publications
8
36
1
1
Order By: Relevance
“…Rats were then tested in behavioral observation cages as described above. Our previous work indicates that CRF infusions into the BLA cause dramatic reductions in feeding and increases in grooming behavior similar to those observed in the present studies with UCN into LS (Jochman et al, 2005). Based on this work, it was predicted that this dose of NBI would reverse the intra-BLA CRF-induced anorexia.…”
Section: Crf Receptor Mediation Of Ls Effects: Blockade Of Ucn-inducesupporting
confidence: 50%
See 2 more Smart Citations
“…Rats were then tested in behavioral observation cages as described above. Our previous work indicates that CRF infusions into the BLA cause dramatic reductions in feeding and increases in grooming behavior similar to those observed in the present studies with UCN into LS (Jochman et al, 2005). Based on this work, it was predicted that this dose of NBI would reverse the intra-BLA CRF-induced anorexia.…”
Section: Crf Receptor Mediation Of Ls Effects: Blockade Of Ucn-inducesupporting
confidence: 50%
“…To verify that the doses of NBI used in the LS were sufficiently high to produce behavioral effects, experiment 8 tested the hypothesis that NBI would block the effects of CRF microinfusion into the BLA, which we previously showed to cause decreases in feeding and increases in grooming similar to those of UCN in the LS (Jochman et al, 2005). Figure 6 displays the results of this experiment.…”
Section: Experiments 8: Crf 1 Receptor Antagonist Does Block Behavioramentioning
confidence: 93%
See 1 more Smart Citation
“…CRH-2 receptor mRNA has been demonstrated to be highly expressed here (Lovenberg et al, 1995). Basolateral amygdala mediates CRH-induced anorexia through CRH-1 receptors (Jochman et al, 2005), while lateral septum and BNST through the CRH-2 receptor (Ohata and Shibasaki, 2011;Smagin et al, 1998). However, pharmacological and neuromorphological studies have demonstrated that Ucn-3 rather than CRH is the most potent and specific endogenous ligand for CRH-2 receptor .…”
Section: Brain Targetsmentioning
confidence: 99%
“…2,25,41,43 Contribution of CRH to the effects of stress on neuronal function within the brain has also been delineated, and demonstrates age-dependent properties. For example, central administration of CRH activates neurons in the amygdala, contributing to anxiety-like behaviors 44,45 as well as to memory consolidation. 46 The peptide modulates neuronal activity in amygdala in a complex manner 47 and, in larger amounts, can lead to hyperexcitability, a kindling effect, and seizures.…”
Section: Introductionmentioning
confidence: 99%